Community Resistance to Socio-Cultural Change in the Perspective of Education - Ratnawati, Etty; Fajar Ardiansyah, Mukhammad; Nur Khovivah, Siti (International Journal on Education Issues, 2025)
Purpose - This study aims to examine the causes and impacts of socio-cultural changes in society that arise from various internal and external factors, as well as analyze the forms of community resistance toward these changes. Design/Methodology/Approach - The research investigates socio-cultural changes by exploring societal reactions such as attachment to traditions, fear of negative impacts, and unpreparedness for technological innovation. It also reviews the role of education and educational strategies in addressing resistance to socio-cultural changes. Findings - The results show that socio-cultural changes generate both positive and negative impacts. Positive impacts include improved quality of life and increased competitiveness, while negative impacts include juvenile delinquency, crime, and social protests. The findings emphasize the need for society to be selective in accepting changes that bring positive influence while limiting negative effects that disrupt social order. Originality/Value - This study contributes by highlighting the importance of selective understanding in dealing with socio-cultural changes to maintain a balance between development and existing traditional values. It also provides insights into educational strategies that can help communities reduce resistance and adapt constructively to socio-cultural transformation.